Empowering Women for Quality Educations - Jesika Puteri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Quality education is a fundamental foundation for human development and national progress. Women play a strategic role in supporting education at both family and community levels; however, they still face various barriers in accessing and participating in quality education. This community service program aims to empower women to support the realization of quality education through a participatory approach. The method employed is a participatory approach with a qualitative descriptive design, involving women actively in socialization, training, group discussions, and educational mentoring activities. The results indicate an increased awareness among women regarding the importance of quality education, improved understanding of women's strategic roles in family education, as well as enhanced self-confidence and participation in community-based educational activities. These changes in attitudes and behaviors serve as initial indicators of the success of women's empowerment in supporting educational quality improvement. The program demonstrates that women's empowerment through participatory approaches and continuous mentoring contributes positively to the development of inclusive and sustainable education at the family and community levels.